Choice of affective partners: influence of sequel of labiopalatal fissure sequela - Brasil, Fernanda Renda; Tavano, Liliam D'Aquino; Caramaschi, Sandro; Rodrigues, Olga Maria Piazentin Rolim (Paidéia (Ribeirão Preto), 2007)
Adolescents, fissured or not, experience new emotions regarding themselves and the opposite sex when they search for affective partners, establishing criteria for this selection. This study aims to know the criteria used by fissured adolescents in selecting affective partners and whether such criteria differ from those employed by their peers. A total of 74 adolescents, both genders, aged 14 to 21 years, answered a questionnaire and were divided in two groups: Fissured (FG) and Not Fissured (NFG). Results suggest there is no expressive difference between groups, considering the characteristics they value in themselves and in others, for choosing affective partners. It was verified that the NFG adolescents give more value to the face than do FG adolescents, presenting statically significant correlation. These results permitted to infer that the fissure partially interferes in the perception of oneself and of the other in the search for affective partners.